Application of game theory for dynamic access control in security systems. (2016) - Zhang, Yixuan; He, Jingsha; Zhao, Bin; Liu, Ruohong
Access control is a core security technology that has been widely used in computer systems and networks. In access control, an object wants to make sure that a subject makes honest access and the subject hopes that access requests will receive permissions from the object. In this paper, we model access control as a repeated game between subject and object and apply game theory to authorise access requests. The purpose is to make honest access to seek more payoffs for subject from the access. The ultimate goal of applying the game theory to access control is to discourage dishonest access from subject so that we can improve the effectiveness of access control, which is achieved through deriving the conditions that would lead to Nash equilibrium. We also perform some experiments to demonstrate the effectiveness of our game theory-based access control and show its advantages over traditional access control models as well.